2016
DOI: 10.18632/oncotarget.13269
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal protein L34 promotes the proliferation, invasion and metastasis of pancreatic cancer cells

Abstract: Ribosomal proteins (RPs) are the main components of ribosomes and participate in the self-assembly of ribosomes and protein synthesis. Recent advance has shown that RPs play important roles in the tumorigenesis and drug resistance of various cancers. However, the expression status and function of RPL34 in pancreatic cancer (PC) remains unclear. In this study, we find that RPL34 is overexpressed in PC tissues and cell lines, which is correlated with decreased methylation of its promoter. Knockdown of RPL34 effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 31 publications
3
20
0
Order By: Relevance
“…For example, the regulatory element harboring rs74450569 presents several TF binding sites, among others, FOSL2 and JUN that are regulated by the ribosomal protein L34 (RPL34) through MAPK and p53 signaling. Silencing of RPL34 has been shown to inhibit tumor growth and proliferation, and simultaneously, to upregulate the expression of several TFs, including FOSL2 and JUN (Wei et al, 2016). A working hypothesis is that this may, in turn, increase the enhancer activity of the regulatory element harboring rs74450569 leading to an increase in DPYD activity and reduced toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the regulatory element harboring rs74450569 presents several TF binding sites, among others, FOSL2 and JUN that are regulated by the ribosomal protein L34 (RPL34) through MAPK and p53 signaling. Silencing of RPL34 has been shown to inhibit tumor growth and proliferation, and simultaneously, to upregulate the expression of several TFs, including FOSL2 and JUN (Wei et al, 2016). A working hypothesis is that this may, in turn, increase the enhancer activity of the regulatory element harboring rs74450569 leading to an increase in DPYD activity and reduced toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have mainly focused on mosquitoes and plants [24] but are rare in cancer development. In the past 3 years, however, increasing studies have demonstrated that RPL34 is deregulated in various types of human cancers, including nonsmall lung cancer, gastric cancer, esophageal cancer and prostate cancer [18][19][20]22]. RPL34 could regulate cell cycle transition by inhibiting Cdk4 and Cdk5 in HeLa cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…RPL34 is a highly conserved protein belonging to the 60S large subunit, which has a zinc finger motif [17]. In several cancers, RPL34 was dysregulated in various cancers, and silencing RPL34 led to inhibition of cell proliferation and migration [18][19][20][21][22][23]. However, there are not enough results to illuminate the role of RPL34 and its clinical significance in hilar cholangiocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the overexpression of the ribosomal protein receptor for activated C kinase (RACK1), a component of the 40S ribosome, significantly inhibited doxorubicin‐induced apoptosis in different hepatocellular carcinoma cell lines, while shRNA‐silencing of RACK1 suppressed tumour growth in combination with doxorubicin (Ruan et al , ). Furthermore, RPL34 is overexpressed in pancreatic cancer patients and the knockdown of RPL34 in pancreatic cancer cells sensitized the tumour cells to gemcitabine and 5‐flourouracil (Wei et al , ). Interestingly, even if ribosome biogenesis occurs in both normal and cancer cells, there is evidence that the inhibition of ribosome biogenesis may cause selective damage to malignant cells (Brighenti et al , ).…”
Section: Discussionmentioning
confidence: 99%